COMPOSITION AND HORIZONTAL STRUCTURE OF THE SHRUSH-TREE COMPONENT OF A SEASONALLY DRY TROPICAL FOREST - SDTF - Costa Júnior, Djailson Silva da; Cunha, John Elton de Brito Leite; Silva, Bruce Kelly da Nobrega; Melo, David Marx Antunes de; Cavalcanti, Maria Luíza Coelho; Pérez Marin, Aldrin Martin (Floresta, 2024)
The objective was to evaluate the floristic composition and horizontal structure of a shrub-tree fragment of Tropical Seasonally Dry Forest - (SDTF), of conserved Caatinga, in the municipality of Campina Grande - PB, Brazil. Located at the Prof. Ignácio Salcedo, at the National Institute of the Semi-Arid Region – (INSA) / Ministry of Science, Technology and Information – (MCTI). In a transect of (50 m x 100 m), with 50 plots of (10 m x 10 m), individuals and stems with CBH ≥ 6 cm were measured. The presence of 2.602 individuals ha-1, with 3.210 stems ha-1, distributed in 17 families, 34 identified genera, 1 unidentified genus and 16 species. The most important families in number of species and individuals were Fabaceae and Apocynaceae, mainly due to the occurrence of the species Cenostigma nordestinum Gagnon & G.P.Lewis and Aspidosperma pyrifolium Mart. & Zucc., respectively. The relevance of the two species with the highest density was perceived in relation to the basal area, which corresponded to 2.12 m2 ha-1 and 1.26 m2 ha-1, respectively, which showed the main contribution of the mentioned families, the area studied in terms of its diversity, was considered a normal pattern with a higher average value of 2.42 nats ind-1, when compared to some studies in the literature. In view of this, this study constitutes basic tools for its management and conservation, enabling the adoption of correct practices, comparisons between and within forest communities, in addition to giving rise to the formulation of hypotheses for other studies.